Greek and Roman mythology - Nardo, Don, 1947- (San Diego, CA : Lucent Books, 1998)
Examines the historical development of Greco-Roman mythology, its heroes, and its influence on the history of Western civilization.
Includes bibliographical references (p. 102-107) and index.
Keywords: Mythology, Classical -- Juvenile literature; Mythology, Classical